2017
DOI: 10.1080/13562517.2017.1391199
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital and performance among undergraduate students: the role of meaning-focused coping and satisfaction

Abstract: She is also the Director of WANT-Research Team High Performance Group. Currently she is the salient President of the Spanish Society of Positive Psychology (SEPP) and she is an Advisor of the International Positive Psychology Association (IPPA) Work and Organizations Division's. She has about 300 national and international publications on Occupational Health Psychology and Positive Psychology applied to work. She has created a project of dissemination to share scientific knowledge and to help people and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 41 publications
6
62
0
2
Order By: Relevance
“…In this regard, Crego, Carrillo-Díaz, Armfield and Romero (2016) established that perceived stress mediated the relationship between coping and performance. Similarly, Ortega-Maldonado and Salanova (2018) found that meaning-focus coping was indirectly related to performance through academic satisfaction. Therefore, there is no clear evidence for a direct relationship between performance and coping.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this regard, Crego, Carrillo-Díaz, Armfield and Romero (2016) established that perceived stress mediated the relationship between coping and performance. Similarly, Ortega-Maldonado and Salanova (2018) found that meaning-focus coping was indirectly related to performance through academic satisfaction. Therefore, there is no clear evidence for a direct relationship between performance and coping.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, if adaptive coping is a personal resource for managing stressful situations, it could be related to performance through academic engagement dimensions. Previous research suggested that performance was indirectly and positively related to adaptive coping (Crego et al, 2016;Struthers et al, 2000;Ortega-Maldonado & Salanova, 2018) but it was indirectly and negatively related to maladaptive emotional coping (Crego et al, 2016). The current study evaluates the possible mediating role of academic engagement in the relationship between coping and academic performance.…”
Section: Introductionmentioning
confidence: 89%
“…This process involves the capacity to negotiate for and draw upon psychological, social, cultural and environmental resources (Brewer et al, 2019, p. 10). The development of resilience has been shown to reduce psychological distress, assist with managing academic demands and enhance academic outcomes (Ortega-Maldonado, & Salanova, 2018;Pidgeon, Rowe, Stapleton, Magyar, & Lo, 2014). Rahat and Ilhan (2016) describe resilience as a significant predictor of successful coping for university students.…”
Section: Introductionmentioning
confidence: 99%
“…University staff play a pivotal role in the development of student capabilities (Chalmers et al, 2014), and thus are ideally placed to help build students' resilience (Ortega-Maldonado & Salanova, 2018). However, barriers exist to staff successfully enhancing student resilience, including the pressures they face on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation